The 20th anniversary of the journal: Editor's introduction - Zavadskas, Edmundas Kazimieras; Antuchevičienė, Jurgita (Journal of Civil Engineering and Management, 2014)
The 20th anniversary of the journal: Editor's introduction. Journal of Civil Engineering and Management, 20(3), pp. 309–310.